2005
DOI: 10.1258/135763305775124939
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of child development services by videoconferencing: A review of four years’ experience in Queensland

Abstract: In 2001 the Child Development Unit (CDU) in Brisbane piloted a series of monthly multidisciplinary case discussions via videoconference in the area of child development. During 2001 two sessions were provided; during 2004 there were 40. The substantial growth in 2004 was due to the expansion of child development services to include special interest group meetings and multipoint case conference meetings. In 2004, a total of 49 h of videoconferencing was conducted. The average session length was 75 min. Educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The P values presented in these studies varied from .002 to .05. However, the two studies in which mortality was the outcome of interest were unable to demonstrate a statistically significant difference in favor of the home telemonitoring group [52-53]. A small RCT [59] and a nonrandomized study [60] did not report P values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The P values presented in these studies varied from .002 to .05. However, the two studies in which mortality was the outcome of interest were unable to demonstrate a statistically significant difference in favor of the home telemonitoring group [52-53]. A small RCT [59] and a nonrandomized study [60] did not report P values.…”
Section: Resultsmentioning
confidence: 99%
“…All 3 small RCTs [51,52,55] reported no significant differences in the number of readmissions or length of stay between the telemonitoring intervention group and the control group receiving usual care On the other hand, the number of readmissions and the number of days of hospitalizations for chronic heart failure among the participants in both cohort studies [57-58] decreased significantly during the 12-month study period ( P <. 001).…”
Section: Resultsmentioning
confidence: 99%
“…The study with the lowest methodological score was a short report and unable to provide detail [30]. Overall the studies had a clear research question and adequately described the educational context and intervention although not with sufficient detail to enable replicability of the research.…”
Section: Methodsmentioning
confidence: 99%
“…One study about infant colic [ 17 ] identified variable content and differences between commercial and non-commercial websites, which may expose parents to conflicting or potentially harmful information. Most of the research literature on Internet provision of health information has focused on the quality and quantity of available information or on delivering health interventions via the Internet or website applications [ 18 ]. Few qualitative studies have investigated the social and cultural meanings of the available information.…”
Section: Introductionmentioning
confidence: 99%
“… Authors’ contributions The idea for this study arose from discussions between RM and PH about the findings of two studies [ 18 , 19 , 39 ], which informed a MRes student project at the University of Stirling for AA. AA is a midwife who conducted the data gathering and analysis as part of a MRes research placement module.…”
mentioning
confidence: 99%